Thromboinflammatory response is increased in pancreas transplant alone versus simultaneous pancreas-kidney transplantation and early pancreas graft thrombosis is associated with complement activation - Kristina Rydenfelt; Kristina Rydenfelt; Kristina Rydenfelt; Gisle Kjøsen; Gisle Kjøsen; Rune Horneland; Judith Krey Ludviksen; Trond Geir Jenssen; Trond Geir Jenssen; Pål-Dag Line; Pål-Dag Line; Tor Inge Tønnessen; et al. (Frontiers in Immunology, 2023)
BackgroundPancreas transplant alone (PTA) recipients are more affected by pancreas graft thrombosis, and graft loss compared to simultaneous pancreas-kidney (SPK) recipients. The pathophysiology is unknown, but an increased immune response has been suggested in the PTA recipients. In this observational study, we compared perioperative thromboinflammation between PTA (n=32) and SPK (n=35) recipients, and between PTA recipients with (n=14) versus without (n=18) early graft thrombosis.MethodsWe measured C-reactive protein (CRP), plasma markers of activated coagulation and complement, and cytokines preoperatively and daily during the first postoperative week.ResultsPreoperatively, coagulation and complement activation markers were comparable between PTA and SPK recipients, while cytokine concentrations were higher in SPK recipients (TNF, IL-8, IP-10, MCP-1, MIP-1α; all p<0.05). On the first postoperative day, PTA recipients had higher coagulation activation, measured as thrombin-antithrombin complex (TAT), than SPK recipients (p=0.008). In the first postoperative week, PTA recipients showed higher relative cytokine release (IL-6, IL-8, G-CSF, IP-10, MCP-1, and MIP-1α; all p<0.05) while SPK recipients showed higher absolute cytokine concentrations (TNF, IL-1ra, IL-8, MIP-1α, and IL-4; all p<0.05). PTA and SPK recipients showed similar terminal complement complex (TCC, sC5b-9) activation. On the first postoperative day, TCC (OR 1.2 [95% CI 1.0-1.5] for 0.1 CAU/ml increase, p=0.02) and CRP (OR 1.2 [95% CI 1.0-1.3] for 10 mg/L increase, p=0.04) were associated with an increased risk of early graft thrombosis. TCC was specific for graft thrombosis, while CRP increased with several complications. PTA recipients with compared to those without graft thrombosis had higher TCC pre- (p=0.04) and postoperatively (p=0.03).ConclusionThe relative increase in postoperative thromboinflammatory response was more pronounced in PTA recipients. Complement activation was associated with an increased risk of graft thrombosis. This study indicates that innate immune activation rather than elevated levels may affect early postoperative pancreas graft thrombosis.Clinical trial registrationhttps://clinicaltrials.gov/ct2/show/NCT01957696, identifier NCT01957696